Secure-System Designers Strive to Stem Data Leaks. - Edwards, Chris (Communications of the ACM, 2015)
The article focuses on the use of side-channel analysis by hackers to reveal secure cryptographic keys and protected data and some countermeasures. It states that the affordable programmable integrated circuit open-source platform Chip-Whisperer has widened the potential user base of hackers using side-channel attacks. It mentions that side-channel analysis focuses on the core algorithm by detecting changes in data processed by algorithms running on a dedicated hardware unit or microprocessor. It comments on the vulnerability of Web application programming interface keys to side-channel attacks and talks about countermeasures against side-channel attacks.